THE EFFECT OF OPEN UNEMPLOYMENT AND EDUCATION ON POVERTY IN INDONESIA - Muhammad Zaky Anwar; Neli Aida; Arivina Ratih Yulihar Taher (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Poverty remains a major challenge in the economic development process in Indonesia. The purpose of this study is to explore more deeply the influence of unemployment and education on the condition of the poor in Indonesia, focusing on the ten provinces that recorded the lowest poverty rates during President Joko Widodo's leadership. This study uses a descriptive quantitative approach with panel data covering the period from 2015 to 2024. The Random Effect Model (REM), which was selected based on the results of the Chow, Hausman, and Lagrange Multiplier tests, was used to perform the analysis with multiple linear regression. The findings of this study show that individually, the variable Open unemployment rate affects poverty positively and significantly, while the education variable affects poverty negatively and significantly. Overall, these two variables have a considerable effect on chemistry. These findings emphasize the importance of implementing policies that focus on effective means of reducing poverty in Indonesia to improve the quality of education and create jobs.